Organizational Diversity Management and Job Satisfaction among Public Servants - Munyeka, Wiza (Journal of Economics and Behavioral Studies, 2014)
The world-wide shift in demographics, changing immigration patterns and social change are all factors that affect the work environment. (Brevis & Vrba, 2014: 194). The demands of globalization, technological innovation, economic imperatives, ecological sensitivity and the need for sustainable development are the challenges that business organizations worldwide face in order to survive. From the human perspective the challenges are about socio-political transformation and especially about managing and celebrating diversity (Magretta, 1999). The diversity aspect of the topic is an important part of the economic landscape in post-apartheid South Africa where phrases like â€œeconomic freedomâ€ are voiced from labor unions and political figures alike. These calls from the likes of Julius Malema, the then leader of the African National Congress Youth League, Zwelinzima Vavi, the General Secretary of the Congress of South African Trade Unions and Matthews Phosa, Treasurer-General of the African National Congress are often the focus of news reports (ANCYL march â€“ Day 2, 2011; Phosa calls for economic freedom, 2012; Vavi, 2012). Almost half the organizations reported that the biggest challenge facing organizations over the next ten years is obtaining human capital and optimizing their human capital investments (HR Magazine. 55, no.11 (November 2010): 80) in Bohlander & Snell (2013: 21). Bohlander & Snell (2013: 21) further answer the question of why is this so? Changes in the demographic makeup of employees, such as their ages, education levels, and ethnicities, are part of the reason why. In this current study, a population study of 50 public servants in a selected public sector industry was used. Data was collected through the administration of the organizational diversity questionnaire and job satisfaction questionnaire. Individuals in the population sample were instructed to complete a questionnaire as a measuring instrument. The copies of ODQ and JSQ were distributed among public servants at a selected public service department.